Home Garden, Desirable Dietary Pattern and Food Expenditure In Banjarnegara Regency - Uni Wuriyaningrum; Istiqomah Istiqomah; Suprapto Suprapto (EKO-REGIONAL, 2020)
The study is based on the patterns of food consumption in the community that has not reached the minimum nutritional standard for activities. This study aimed to determine the impact of the Sustainable Food House Area (KRPL) Program on DDP score, energy consumption, protein consumption and household foodstuff expenditure in Banjarnegara Regency. Primary data were obtained from the KRPL and non-KRPL benefidciaries. Secondary data were obtained from Food Security Agency of the Ministry of Agriculture, the Central Java Province Food Security Department and the Banjarnegara Regency Food Security Department. The analytical tool used t-test between the KRPL beneficiary group and the non-KRPL beneficiary group. The analysis result indicated that there were significant differences in DDP scores, energy consumption, and foodstuff expenditure between the KRPL and non-KRPL groups. DDP score of KRPL group was higher than non-KRPL group. This indicated that consumption of the KRPL group was more diverse and nutritionally balanced. The energy consumption of the KRPL group was higher than the non-KRPL group, so that the energy adequacy of the KRPL group was closer to the recommended dietary allowance. Protein consumption in the KRPL group was higher and has met the recommended dietary allowance, while the non-KRPL group has not met the recommended dietary allowance. The foodstuff expenditure in the KRPL group was lower than the non-KRPL group because there were savings on the foodstuff expenditure. Thus, the KRPL Program has an impact on increasing DDP scores, energy consumption and savings on household food expenditure. Keywords : Sustainable Food House Area (KRPL), energy consumption, protein consumption, foodstuff expenditure, DDP score.